PENGARUH KEMAMPUAN KONEKSI MATEMATIS SISWA TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI GAYA BELAJAR PADA MATERI BANGUN RUANG SISI DATAR SISWA KELAS IX SMP DI KOTA METRO - Santi Widyawati (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
This research was aimed at finding out the inflence of the ability of koneksi matematis through the studentsâ€™ learning result viewed from the students leaning style in learning Bangun Ruang Sisi Datar at the IX grader of all Junior high school in metro. This research was an experiment research design which was conducted in the form of True Experimental Design. Of faktorial 3 Ã— 3. The population of this research was the eight graders of all Junior high School, in the academic year of 2015/2016 . the sampling technique of the research is stratified cluster random sampling. The sample of the research consist of 278 students that consist of 90 male students which consist of 90 male students and 95 female students. The result of this research is (1) students with high mathematic conection have a good learning result than those having medium and low one, while students with medium mathematic conection have a good learning result than those having low one, (2) students with visual learning style and the students with kinesthetic lerning style, both of them have the same learning resut but the learning result both of them is higher than auditorial learning style (3) in each type of learning style, students with high mathematic conection have a good learning result than those having medium and low one, while students with medium mathematic conection have a good learning result than those having low one, (4) in each mathematic conection categories (high, medium and low) students with visual learning style and the students with kinesthetic lerning style, both of them have the same learning resut but the learning result both of them is higher than auditorial learning style. Kata Kunci: connection mathematic ability and learning style